Officials Reflections about Health Promoting Factors among Newly Arrivals : An Introductory Analysis - Carlerby, Heidi; Persson, Mats (International Journal of Community & Family Medicine, 2017)
Background: Resulting from conflicts, millions of peoples have been forced to leave their countries of origin. In Sweden, the Employment Agency is responsible for making decisions of immigrants’ residence in municipalities and in co-operation with these allow the immigrants’ establishment in the society. Preventive interventions among migrants and refugees, and health interventions in heterogeneous populations show that increased participation in society has positive imprints on health development. A new country includes getting acquaintance with non-familiar cultures. For example, other expectations on rules of gender, sickness, and illness. Recent years the low density populated areas in northern Sweden have received a high number of refugees in comparison with their population size. The purpose of this study was to explore how officials the Employment Agency and a selection of municipalities reflect over and define health promoting factors in their meetings with newly arrived. Methods: All officials (N 68) in one of the four northern counties were invited to recording their reflections on health promoting factors close to their meetings with newly arrived. The officials recorded how they defined health promoting factors according to the Audit method. The data collection of experiences of importance considering health promotion and social determinants was collected by five focus group interviews with twenty-three officials. Results: This study showed that the officials defined access to the health care, participation in the society, and sufficient collaboration between the authorities for not losing valuable time during the establishment period as imported factors for their clients’ opportunities for health. The officials take power among males for given, while they more often reflected over lack of power among women. However, the Swedish ideal of gender as equal quite often a challenge the newly arrivals.